Identifying Traits Associated With Terminal Drought Tolerance in Sesame (Sesamum indicum L.) Genotypes - Pandey, Brij Bihari; Ratnakumar, P.; Usha Kiran, B.; Dudhe, Mangesh Y.; Lakshmi, G. Sowjanya; Ramesh, Kulasekaran; Guhey, Arti (Frontiers in Plant Science, 2021)
Sesame is predominantly cultivated in rainfed and low fertile lands and is frequently exposed to terminal drought. Sesamum species inhabiting dryland ecosystems adaptively diverge from those inhabiting rainfed habitats, and drought-specific traits have a genetic basis. In sesame, traits associated with drought conditions have not been explored to date, yet studies of these traits are needed given that drought is predicted to become more frequent and severe in many parts of the world because of climate change. Here, 76 accessions from the available Indian core set were used to quantify variation in several traits under irrigated (WW) and terminal drought stress (WS) conditions as well as their association with seed yield over two consecutive years. The range of trait variation among the studied genotypes under WW and WS was significant. Furthermore, the traits associated with seed yield under WW and WS differed. The per se performance of the accessions indicated that the expression of most traits was reduced under WS. The correlation analysis revealed that the number of branches, leaf area, leaves dry weight, number of capsules plant-1, and harvest index were positively correlated with seed yield under WW and WS, and total dry matter, plant stem weight, and canopy temperature were negatively correlated with seed yield under WW and WS, indicating that smaller and cooler canopy genotypes had higher yields. The genotypes IC-131936, IC-204045, IC-204861, IC-205363, IC-205311, and IC-73576 with the highest seed yields were characterized by low canopy temperature, high relative water content, and high harvest index under WS. Phenotypic and molecular diversity analysis was conducted on genotypes along with checks. Phenotypic diversity was assessed using multivariate analysis, whereas molecular diversity was estimated using simple sequence repeat loci to facilitate the use of sesame in breeding and genetic mapping. Simple sequence repeats showed low allelic variation, as indicated by a low average number of alleles (2.31) per locus, gene diversity (0.25), and the polymorphism information content (0.22). Cluster analysis (neighbour-joining tree) revealed three major genotypic groups and structure analysis showed 4 populations. The diverse genotypes identified with promising morpho-physiological traits can be used in breeding programs.